Impact of Corporate Governance and Financial Leverage on the Value of Nepalese Commercial Banks - Kami, Dilip Kumar; Acharya, Dipendra Raj; Dutta, Kaushal; Bhatt, Nilam; Bist, Nirajan (Nepalese Journal of Finance, 2025)
The study examines the impact of corporate governance and financial leverage on the value of Nepalese commercial banks. Return on assets and market price per share are the dependent variables. The selected independent variables are board size, independent ownership, audit committee, debt to total assets, debt to total equity, institutional ownership and board diversity. The study is based on secondary data of 13 commercial banks with 104 observations for the study period from 2015/16 to 2022/23. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB), and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance and financial leverage on the value of Nepalese commercial banks. The study showed that board size has a positive relationship with return on assets. It indicates that increase in board size leads to increase in the return on assets. On other hand, audit committee has a positive relationship with return on assets. It indicates that increase in number of audit committee leads to increase in the return on assets. Similarly, debt to assets ratio has a negative relationship with return on assets. It indicates that increase in debt to assets ratio leads to decrease in the return on assets. Similarly, institutional ownership has a negative relationship with return on assets. It indicates that increase in percentage of institutional ownership leads to decrease in the return on assets. Debt to total assets have a positive relationship with market price per share. It indicates that increase in ratio of debt to total assets, leads to increase the market price per share. Similarly, debt to total equity has positive relationship with market price per share and return on assets. It indicates that increase in debt to total assets ratio, leads to increase in market price per share and return on assets. Further, the institutional ownership has positive relationship with market price per share. It indicates that increase in percentage of institutional ownership leads to increase in market price per share. However, board size has a negative relationship with market price per share. It indicates that increase in board size leads to decrease in the market price per share and return on assets. Likewise, the number of independent directors have negative relationship with market price per share and return on assets. It indicates that increase in number of independent directors leads to decrease the market price per share and return on assets. Audit committee size has a negative relationship with market price per share. It indicates that increase in number of audit committee leads to decrease in the market price per share and return on assets.